Cadmium toxicity alleviation through exogenous application of gibberellic acid (GA3) in mustard (Brassica juncea (L.) czern.) and rapeseed (Brassica rapa L.) - Iqbal, Muhammad Sajjad; Bashir, Faiza; Muhammad, Akbar; Ahmad, Khawaja Shafique; Ali, Muhammad Azhar; Hussain, Syed Atiq; Arshad, Noshia; Masood, Hajra; Munir, Saba; Ahmad, Tahira; Islam, Muhammad (Universiti Kebangsaan Malaysia, 2022)
An experiment was carried out by considering adverse impact of heavy metals on human health through consumption of crops. To alleviate the adverse effects of cadmium (Cd) toxicity through foliar application of gibberellic acid (GA3), two varieties of Brassica including Indian mustard (Brassica juncea (L.) Czern.) commonly known as ‘Raya’ and rapeseed (Brassica rapa L.) as ‘Toria’ were studied. The Completely Randomized Design (CRD) was used with eight treatments including control in four replicates. Treatments were as following, T0 (control), T1 (150 μM CdCl2), T2 (50 mg/L GA3), T3 (75 mg/L GA3), T4 (100 mg/L GA3), T5 (150 μM CdCl2 + 50 mg/L GA3), T6 (150 μM CdCl2 + 75 mg/L GA3), and T7 (150 μM CdCl2 + 100 mg/L GA3). Gibberellic acid (GA3), a plant growth regulator applied exogenously. The concentration of cadmium (150 μM CdCl2) resulted in Cd toxicity affected adversely the morphological and biochemical parameters. Foliar application of GA3 (50 mg, 75 mg and 100 mg) positively influenced the various growth parameters as root length (30 cm), shoot length (129.75 cm), number of leaves (14.5), pods per plant (88) and biochemical parameters like total chlorophyll (0.19 mg/g), protein content (0.70 mg/mL), carbohydrates (0.37 mg/mL) and CAT (0.56 units/mg). Outcome indicated that GA3 reduces the harmful effects of Cd stress in both varieties. It was concluded that all growth and yield parameters of variety ‘Raya’ were better as compared to variety ‘Toria’, hence Raya recommended for large scale cultivation with GA3 under Cd stress.